Plasmon Resonance in A-С : Н Films Modified with Platinum Nanoclusters - O. Prikhodko; N. Manabaev; N. Guseinov; S. Maksimova; E. Muhametkarimov; S. Mikhailova; E. Daineko (Журнал нано- та електронної фізики)
Optical density spectra of amorphous diamond-like films of hydrogenated carbon modified with platinum impurity (a-C : HPt) have been investigated. a-C : HPt films were prepared by the method of ion plasma magnetron co-sputtering of graphite and platinum in argon-hydrogen atmosphere. Platinum content in the films was varied from 0 to 9 at. %. In the optical spectra of a-C : HPt films with different Pt content the peaks of resonance absorption in the range from 496 to 501 nm were found, whilst in the spectrum of a-C : H films the absorption peak is absent. The appearance of these absorption peaks in a-C : HPt films is explained by resonance plasmon vibrations of free electrons in platinum nanoclusters. The average diameter of the Pt nanoclusters was estimated using electromagnetic theory of Mie, and it is ~ 5 nm.